Non-destructive measurement of the tungsten content in the binder phase of tungsten heavy alloys. (June 2018) - Marschnigg, S.; Gierl-Mayer, C.; Danninger, H.; Weirather, T.; Granzer, T.; Zobl, P.
Abstract: Measurement of the magnetic properties is well-established to non-destructively monitor composition and microstructure of cemented carbides. The present study demonstrates that this method can also be applied to ferromagnetic tungsten heavy alloys. Compositional changes during heat treatment may have effects on the magnetic properties of W-Ni-Fe heavy alloys, as an example, which would allow for simple non-destructive measurement. We report that increasing tungsten content in Ni-Fe(-W) samples and higher annealing temperatures for Densimet 180 ® grade 95W-Ni-Fe heavy alloy samples cause a decrease of their respective weight-specific saturation magnetization. XRD analyses show that higher heat treatment temperatures result in larger lattice parameters of the binder phase. Likewise, larger amounts of tungsten dissolved in the nickel-iron samples also widen the γ-Ni-Fe lattice. This suggests that the decrease in saturation magnetization of heavy alloys annealed at higher temperatures is caused by more dissolved tungsten in the binder phase. As EDX measurements may overestimate the tungsten concentration in the binder phase, another method for determining the amount of dissolved tungsten was developed. A relationship between saturation magnetization and tungsten content in the binder could be established through the Ni-Fe(-W) samples with known amounts of tungsten. In view of these results, we propose saturation magnetization measurements as a simple non-destructive tool for additional quality control in the production of ferromagnetic tungsten heavy alloys. Highlights: Heat treatment temperature affects saturation magnetization of W-Ni-Fe heavy alloy. Tungsten content in binder can be estimated from saturation magnetization. The presented method allows for monitoring composition changes after annealing.